Thoth 2.0: Advancing an RSL Tool for Enhanced Snowballing Support - Comis, Diego; Rodrigues, Elder de Macedo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.11616, 2025)
Thoth is an open-source, web-based tool designed to support researchers in conducting Systematic Literature Reviews (SLRs) by automating critical phases of the review process. Currently in its final testing and refinement stage, the tool introduces an advanced Snowballing module that systematically identifies relevant studies through backward and forward citation analysis, integrated with the CrossRef API for reliable metadata retrieval. By automating repetitive tasks, including study selection, quality assessment, and data extraction, Thoth 2.0 significantly reduces manual effort while minimizing human error. Its user-friendly interface supports collaborative workflows, enabling geographically dispersed teams to coordinate SLRs seamlessly. As a freely available solution, Thoth 2.0 addresses key limitations of existing SLR tools, offering a unified platform that combines automation, rigorous methodology, and adaptability to diverse research needs. Its Snowballing module, in particular, extends literature coverage with minimal researcher intervention, demonstrating the tool’s potential to enhance the efficiency and reproducibility of evidence synthesis. Thoth demo video:  https://doi.org/10.5281/zenodo.15493167